1993
DOI: 10.1039/dt9930003031
|View full text |Cite
|
Sign up to set email alerts
|

Bis(η-cyclopentadienyl)imido compounds of niobium

Abstract: The compound [Nb(q-C,H5),(NBut)CI] has been synthesised and its crystal structure determined. It is the precursor for the new compounds [Nb(q-C,H5),(NBut)Me],[Nb(q-C5H5),(NBut)Br], [Nb(q-C5H5),(NBut) (C,H,CH,)]and [Nb(q-C5H5),(NBut)(o-C,H5)], and the hydrido derivative [Nb(q-C5H5)2(NBUt) HI.We have been interested in studying compounds containing both the q-cyclopentadienyl ligand and organoimido ligands :NR since we anticipate that this ligand combination will give rise to interesting reactivities. We and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 19 publications
2
28
0
2
Order By: Relevance
“…[24,25,30] We have expanded this field by the preparation of the following new [53] The synthetic pathway to these complexes is determined by the reaction of the appropriate magnesium reagent MgRCl with the corresponding metallocene complex [Equation (8)]. (8) In the 1 H NMR spectra of the ethyl complexes 16 and 19 ( Figure 6) the ethyl group displays an A 3 BC pattern with typical values of J AB ϭ 7.0, J AC ϭ 7.5, J BC ϭ 14.0 Hz, similar to those reported previously in two ethyl complexes of niobium.…”
Section: Alkyl Derivativesmentioning
confidence: 99%
“…[24,25,30] We have expanded this field by the preparation of the following new [53] The synthetic pathway to these complexes is determined by the reaction of the appropriate magnesium reagent MgRCl with the corresponding metallocene complex [Equation (8)]. (8) In the 1 H NMR spectra of the ethyl complexes 16 and 19 ( Figure 6) the ethyl group displays an A 3 BC pattern with typical values of J AB ϭ 7.0, J AC ϭ 7.5, J BC ϭ 14.0 Hz, similar to those reported previously in two ethyl complexes of niobium.…”
Section: Alkyl Derivativesmentioning
confidence: 99%
“…15 it was reported that this is also the region where the hydride signal of terminal Nb-H 16 and Ta-H 17 bonds are observed for this type of dicyclopentadienyl imido complexes. The difference between the 13 C quaternary and methyl carbon resonances of the tertbutylimido group is 30.8 ppm suggesting a linear disposition of the Nb-N-tBu ligand in complex 15.…”
Section: Methodsmentioning
confidence: 99%
“…[24] In the 1 H NMR spectra of silyl hydride complexes 3 the hydride resonates in the range 1.65-3.00 ppm, down-field shifted as a result of the anisotropy of the Nb=N bond. [25] The hydride bands in the IR spectra are observed in the range 1616-1681 cm…”
mentioning
confidence: 99%